IMPLEMENTASI PENGAWASAN AKADEMIK OLEH PENGAWAS SEKOLAH DASAR SE-KECAMATAN PADEMAWU - Hurriyatul Ifadhah; Nailatul Hasanah; Ali Nurhadi; Rinta Ratnawati (re-JIEM (Research Journal of Islamic Education Management), 2022)
Supervision is a control function that really needs to be carried out by every institution, especially elementary schools. Because every educator and education staff requires development of the tasks carried out. So that supervision can be a benchmark or evaluation material for teachers and education staff. In this study, the researcher used a descriptive qualitative method which resulted in the implementation of academic supervisors by elementary school supervisors in the Pademawu District, namely supervisors providing guidance to each elementary school in Pademawu District. The coaching is in the form of academic coaching and behavioral coaching. The inhibiting factors and supporting factors for academic supervisors by elementary school supervisors in the Pademawu sub-district are collaboration between supervisors and all educators and education staff in elementary schools in the Pademawu sub-district. So that this collaboration can create a sense of togetherness that can support the implementation of supervision to the fullest. However, in practice, the Pademawu regional coordinating supervisor only had two people to handle 53 elementary schools. So that this becomes an inhibiting factor for the implementation of elementary school academic supervisors in the Pademawu sub-district.